Learnings from other perspectives and responses to abuse & mistreatment of vulnerable populations: Elder Abuse, Domestic Violence, Child Protection & Safeguarding People with Disabilities - Blundell, Barbara; Chung, Donna; Budiselik, Bill (2016)
Abuse and mistreatment are common themes across the lifespan, yet our theoretical perspectives, policies and practice interventions are typically targeted to specific vulnerable populations such as older people, women and children in domestic settings, and people with disabilities. Responses and approaches to intervening are also shaped by historical developments in the field of work, including the professional perspectives of those who first ‘discovered’ the issue and developed ways of understanding and dealing with it. For example, elder abuse was first described as ‘granny battering’ (Baker, 1975) and picked up by nurses and medical practitioners who thus framed responses emphasising physical abuse within the health care system.